Documentation: The Project of the Provincial Labour Code

(untitled) (Département des relations industrielles de l’Université Laval, 1949)
The project of the Labour Code presented to the Quebec Legislature with the Bill No. 5 is now history. As this legislative project had considerable scope, various opinions on the subject were expressed and it was withdrawn. We are therefore publishing, as a matter of record, the declaration of the Honourable Antonio Barrette, Minister of Labour, at the time Bill No. 5 was withdrawn, as well as that of the Canadian and Catholic Confederation of Labour and of the Ecclesiastical Commission of Social Studies. It will be noticed that the text of the Ecclesiastical Commission of Social Studies was not sent to the newspapers but to the Members of the Legislative Assembly. The Members of this Commission are: the Revd. Paul Emile Bolté, p.s.s., Professor of Social Sciences in the Faculty of Theology at the University of Montreal; the Revd. Father Emile Bouvier, s.j., Director of the Industrial Relations Section of the University of Montreal and moral adviser of the « Association Professionnelle des Industriels »; the Revd. Father Jacques Cousineau, s.j., moral adviser of the Central Council of the National Syndicates of Montreal and of various Federations affiliated to the Canadian and Catholic Confederation of Labour; the Revd. Gérard Dion, Assistant-Director of the Department of Industrial Relations of Laval University, moral adviser of the employers' associations of the Diocese of Quebec; the Revd. Omer Genest, moral adviser of the National Catholic Syndicates, Diocese of Chicoutimi and the Revd. Henri Pichette, general moral adviser of the Canadian and Catholic Confederation of Labour.